The Intersection of Waqf and Entrepreneurship: Insight from A Bibliometric and Content Analysis Study (Ekonomi Syariah IAIN Kudus, 2024)
The concept of waqf, one of the Islamic philanthropic instruments, has changed over time and has become a tool for passive charity and economic empowerment. This research examines the potential for integrating waqf with entrepreneurship as a social and economic empowerment instrument, using a bibliometric and content analysis approach to identify trends, insights, and gaps in the literature. The research results show that the concept of productive waqf, if managed innovatively, can contribute significantly to sustainable economic development, poverty alleviation, and community empowerment, especially in Muslim-majority countries. This research also highlights the importance of technology-based waqf management, such as sharia fintech and crowdfunding, as well as cross-sector collaboration to increase the social impact of waqf. Recommendations are provided to practitioners, policymakers, and academics, including the need to develop policies that support transparent waqf management, training for nazhir, and further research to explore the potential of waqf in various economic sectors. This study provides theoretical and practical contributions to more innovative and sustainable waqf management.